2019
DOI: 10.3389/fnhum.2019.00355
|View full text |Cite
|
Sign up to set email alerts
|

Head Down Tilt Bed Rest Plus Elevated CO2 as a Spaceflight Analog: Effects on Cognitive and Sensorimotor Performance

Abstract: Long duration head down tilt bed rest (HDBR) has been widely used as a spaceflight analog environment to understand the effects of microgravity on human physiology and performance. Reports have indicated that crewmembers onboard the International Space Station (ISS) experience symptoms of elevated CO2 such as headaches at lower levels of CO2 than levels at which symptoms begin to appear on Earth. This suggests there may be combinatorial effects of elevated CO2 and the other physiological effects of microgravit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 49 publications
7
65
0
Order By: Relevance
“…At p < 0.0005 and k = 10, there were no regions of intercept or slope difference between the SANS and no-SANS participants. We previously found that SANS individuals increased their reliance on visual information during balance from pre-to post-HDBR + CO 2 (Lee et al, 2019a); that is, SANS subjects had greater increases in their ratio of eyes open balance compared to eyes closed balance. Here we identified multiple frontal, parietal, temporal, and occipital regions where the SANS subjects showed stronger correlations with this balance ratio score compared to the no-SANS subjects (Figure 8 and Table 7).…”
Section: Sans Vs No-sans Group Differencesmentioning
confidence: 94%
See 3 more Smart Citations
“…At p < 0.0005 and k = 10, there were no regions of intercept or slope difference between the SANS and no-SANS participants. We previously found that SANS individuals increased their reliance on visual information during balance from pre-to post-HDBR + CO 2 (Lee et al, 2019a); that is, SANS subjects had greater increases in their ratio of eyes open balance compared to eyes closed balance. Here we identified multiple frontal, parietal, temporal, and occipital regions where the SANS subjects showed stronger correlations with this balance ratio score compared to the no-SANS subjects (Figure 8 and Table 7).…”
Section: Sans Vs No-sans Group Differencesmentioning
confidence: 94%
“…passed a minimum physical fitness standard (i.e., an Air Force Class III equivalent physical examination) to participate (Lee et al, 2019a).…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent long-duration head-down tilt studies have shown potential for recreating SANS signs in terrestrial cohorts 51 . However, SANS is considered a pathology unique to spaceflight.…”
Section: Spaceflight-associated Neuro-ocular Syndromementioning
confidence: 99%